PENINGKATAN KETERAMPILAN MEMBACA CEPAT DENGAN TEKNIK SKIMMING - Amalia, Falina Noor (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2019)
A B S T R A C T This research is a CAR designed to improve speed reading skills with skimming techniques of second semester students in Indonesian Language and Literature Education Study Program FKIP UTP. The research design uses the Kemmis and Taggart models which consist of planning, action, observation, and reflection. The data collection technique of this research is in the form of observation and interviews. The level of success of this study is the reading speed of students reached 350 kpm with the percentage of reading comprehension of 70%. Based on the results, the average speed of student reading on pre-cycle is 153 kpm, in cycle I is 258 kpm, and in cycle II is 351 kpm. Furthermore, for the pre-cycle reading comprehension level is 37%, in the first cycle is 64%, and in the second cycle is 73%. Besides that, it was proven that positive changes occurred based on observations and interviews.